Uma experiência pedagógica com a ginástica circense no clube de protagonismo : a educação física e a educação integral - Lara, Natália Bianca Bruni de (2023)
Physical Education has suffered many modifications along its history, frequently changing itself, especially regarding its objectives, intentions, and objects of knowledge to be taught by it, either by the requirements expressed in the legal documents governing National Basic Education or by the essentiality in providing diverse, creative, welcoming and more meaningful experiences to 21st-century students. Thus, it is up to Physical Education to promote different bodily manifestations that stimulate students' curiosities in order to diversify and improve their bodily, cognitive, social and affective repertoires, motivating them to participate collaboratively in the process of building their knowledge, finding in circus gymnastics the possibility of arousing the interest of participants, as well as encouraging the development of autonomy and youth protagonism. This investigation aims to implement actions that enable reflection about the constitution of circus gymnastics as an object of knowledge of Physical Education classes and other areas that the school has, integrating all participants in the research. Circus gymnastics is one of the elements that constitute the Body Culture of Movement and implicitly make up general gymnastics, according to the National Common Curricular Base, has the purpose of providing body experiences through acrobatic possibilities, performative and expressive. This work caused the experiment of circus gymnastics as the content of Physical Education in the school context, through a Protagonism Club, composed of students of the 1st, 2nd, and 3rd years of High School, actions to promote the historical, social and cultural recovery, together with the experience of circus practices adapted to the educational environment. The methodology selected to support this investigation was the qualitative approach of the research-action type, with the use of daily field instruments, systematic observation script (from photographs and filming), and a final questionnaire composed of general questions. The meetings were initiated from a diagnostic survey and followed with the conclusion of the proposal through the collaborative participation of students, who selected the body elements of circus gymnastics to be contemplated throughout the Protagonism Club, being the aerial acrobatics through the acrobatic fabric, the soil acrobatics, the malabar, the magic and the dramatizations with the clown. As well as the organization and presentation of a show to the school community, finalizing the proposal through a collective evaluation, where students could analyze the actions promoted throughout the club, highlighting their considerations. At the end of the study, it was noticed that the students built and enhanced knowledge related to circus gymnastics and improved their physical, expressive, cognitive, and social.